Epistemologi Sebagai Fondasi Ekonomi Islam: Pendekatan Ihtisan, Maslahah Mursalah dan Al-’Urf - Ahmad Wahyudi Zein; Annisa Febrianda; Rania Atikah Putri; Siti Nurhaliza (Jurnal Bisnis, Ekonomi Syariah, dan Pajak, 2024)
This research examines epistemology as a foundation in Islamic economics through the Ihtisaan, Maslahah, Murlahah, and Al-Urf approaches. Epistemology in Islamic economics does not only focus on technical aspects, but also explores the philosophical foundations underlying this system. With this approach, this research seeks to answer the challenges of implementing sharia principles in a modern economic system without ignoring basic Islamic values. The method used is qualitative with a literature study approach, which includes analysis of verses from the Koran, Hadith and the views of ulama. The research results show that these four values ​​complement each other, creating harmony between the normative principles of sharia and practical reality. This concept allows Islamic economics to remain relevant in facing global challenges, providing fair and sustainable solutions. It is hoped that this research can strengthen the position of Islamic economics as a system that is adaptive, inclusive, and remains rooted in the noble values ​​of sharia.